Consumerism and Environmental Nuisance in How to Get Filthy Rich in Rising Asia - Mehvish Muzaffar; Dr. Muhammad Asif; Talha Basheer; Mehreen Zafar; Dr. Sadaf Siddiq; Shumaila Aman (Al-Qanṭara, 2022)
The study aims to analyze Mohsin Hamid’s novel “How to Get Filthy Rich in Rising Asia” (2013) from the perspective of consumerism and “Environmental Nuisance” (Baudrillard 1998). Consumerism has become the cause of environmental nuisance that is defined as the polluted environment, extinction of villages, unending process of urbanization, social alienation, etc. This qualitative research work employs Jean Baudrillard’s conception of consumerism and environmental nuisance and the methodology adopted in this research work is hermeneutic of situation. This study is significant because it is a contemporary and post-postmodern critique of Pakistani society from the point of view of ecocriticism. The study concludes that the consumer culture is promoted by capitalist and it causes a lot of damage to our shared environment. Key Words: Consumerism, Environmental Nuisance, Value, Capitalism, Post postmodernism